Penerapan Firewall Pada Sistem Keamanan Jaringan Komputer Di Sekolah Smk Negeri 5 Seluma - Nopri Dwipoyono; Khairil Khairil; Aji Sudarsono (UNIVED Press, 2023)
Abstract- The Seluma 5 State Vocational High School does not yet have a firewall, so the computer network security at school is still very minimal, both in terms of limiting access to the network. Besides that, internet access at Seluma 5 State Vocational High School is used by teachers and staff to access internet pages by browsing to get information, but there are several teachers and staff who access social media pages and other pages which decreases the effectiveness of the performance of these teachers and staff. Implementation of a Firewall on a computer network security system at the Seluma 5 Vocational High School uses Iptables to monitor packet data traffic processes in the network. With iptables, you can manage network traffic on the server such as allowing, blocking or skipping incoming and outgoing connections, managing ports and so on on the Seluma 5 State Vocational High School Computer Network. Based on the tests that have been carried out, it can be concluded that the implementation of a firewall on the computer network security system at the State Vocational High School 5 Seluma is able to block the ping of death attack and is also able to open and close access to several ports in the network and block the websites facebook.com, instragram .com, and tokopedia.com